Deficiency of Omentin-1 leads to delayed fracture healing through excessive inflammation and reduced CD31hiEmcnhi vessels. (20th August 2021) - Feng, Shi-Kai; Chen, Tuan-Hui; Li, Hong-Ming; Cao, Jia; Liu, Dong-Biao; Rao, Shan-Shan; Liu, Jiang-Hua; Zhang, Yan; Wang, Zhen-Xing; Li, You-You; Tan, Yi-Juan; Liu, Yi-Wei; et al.
Abstract: Fracture healing is a complicated process affected by many factors, such as inflammatory responses and angiogenesis. Omentin-1 is an adipokine with anti-inflammatory properties, but whether omentin-1 affects the fracture healing process is still unknown. Here, by using global omentin-1 knockout ( omentin-1 −/− ) mice, we demonstrated that omentin-1 deficiency resulted in delayed fracture healing in mice, accompanied by increased inflammation and osteoclast formation, and decreased production of platelet-derived growth factor-BB (PDGF-BB) and osteogenesis-promoting vessels that are strongly positive for CD31 and Endomucin (CD31 hi Emcn hi ) in the fracture area. In vitro, omentin-1 treatment suppressed the ability of the tumor necrosis factor-α (TNF-α)-activated macrophages to stimulate multi-nuclear osteoclast formation, resulting in a significant increase in the generation of mono-nuclear preosteoclasts and PDGF-BB, a pro-angiogenic protein that is abundantly secreted by preosteoclasts. PDGF-BB significantly augmented endothelial cell proliferation, tube formation and migration, whereas direct treatment with omentin-1 did not induce obvious effects on angiogenesis activities of endothelial cells. Our study suggests a positive role of omentin-1 in fracture healing, which may be associated with the inhibition of inflammation and stimulation of preosteoclast PDGF-BB-mediated promotion of CD31 hi Emcn hi vessel formation. Highlights: Omentin-1 can promote the recovery of mechanical properties during fracture healing. Omentin-1 can promote the formation of CD31 hi Emcn hi vessels during fracture healing. Omentin-1 can promote fracture healing by inhibiting excessive inflammation.